2012
DOI: 10.4319/lo.2012.57.6.1673
|View full text |Cite
|
Sign up to set email alerts
|

Episodic vertical nutrient fluxes and nearshore phytoplankton blooms in Southern California

Abstract: Three distinct phytoplankton blooms lasting 4-9 d were observed in approximately 15-m water depth near Huntington Beach, California, between June and October of 2006. Each bloom was preceded by a vertical NO 3 flux event 6-10 d earlier. NO 3 concentrations were estimated using a temperature proxy that was verified by comparison with the limited NO 3 observations. The lower-water-column vertical NO 3 flux from vertical advection was inferred from observed vertical isotherm displacement. Turbulent vertical eddy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 54 publications
(88 reference statements)
1
38
0
Order By: Relevance
“…These rates are consistent with, and higher than, growth rates from further offshore (Landry et al 1995(Landry et al , 2009) and from the nearshore environment (Omand et al 2012). Growth rates were M A N U S C R I P T…”
Section: Phytoplankton Growth Potentialsupporting
confidence: 67%
“…These rates are consistent with, and higher than, growth rates from further offshore (Landry et al 1995(Landry et al , 2009) and from the nearshore environment (Omand et al 2012). Growth rates were M A N U S C R I P T…”
Section: Phytoplankton Growth Potentialsupporting
confidence: 67%
“…Several previous studies have identified a linear nitratetemperature (NO 3 -T ) relationship beneath the nitratedepletion density in the California Current region (Strickland, 1970;Parnell et al, 2010;Omand et al, 2012). Profiles of NO 3 -σ t in the spatially averaged quarterly CalCOFI record appear relatively consistent over time (green segments, Fig.…”
Section: Nitrate-density Fits From the California Current Region (Calmentioning
confidence: 93%
“…Garside and Garside (1995) used a stepwise polynomial method to predict nitrate from temperature and salinity during regional phenomena, such as the North Atlantic spring bloom and El Niño/La Niña conditions in the central Pacific. Finally, firstorder linear regressions between nitrate and temperature have been used to predict nitrate in upwelling zones (Traganza et al, 1987;Dugdale et al, 1997;Olivieri and Chavez, 2000;Omand et al, 2012), although mixing and interleaving of water masses may confound this approach (Friederich and Codispoti, 1981). In coastal California, the relationship has been used to predict coastal nitrate concentration over the last century as an indicator of giant-kelp health (Parnell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Water temperature variations play a critical ecological role in the nearshore and are linked to variation in mussel and barnacle growth rates [Phillips, 2005], egg mass production rates of the coastal crab Cancer setosus [Fischer and Thatje, 2008], and barnacle recruitment rates [Broitman et al, 2005]. Temperature is also a tracer for nutrient delivery to coastal waters [e.g., Omand et al, 2012]. Pathogen ecology in swimming waters is affected by temperature, including Staphylococcus [Goodwin et al, 2012], Enterroccus [Halliday, 2012], and Campylobacter [Hokajarvi et al, 2013].…”
Section: Introductionmentioning
confidence: 99%